2000
DOI: 10.1080/01140671.2000.9514122
|View full text |Cite
|
Sign up to set email alerts
|

Weed management practices in apple orchards and vineyards in the South Island of New Zealand

Abstract: A survey of weeds and weed management practices was conducted during 1997/98 in apple orchards and vineyards of Canterbury and Nelson/Marlborough regions of New Zealand. According to growers, mallow (Malva spp.) ranked as the most widespread weed in apple orchards of both regions. In vineyards, mallow was the most common weed in Nelson/Marlborough and the second most common weed in Canterbury. Other dominant weeds in Nelson/Marlborough included grasses, black nightshade (Solarium nigrum), fathen (Chenopodium a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 8 publications
2
20
0
1
Order By: Relevance
“…The results of the present study were also consistent with the results of the studies carried out different region in the world (Dastgheib and Frampton, 2000; Harrington et al, 2002;Hamma and Ibrahim, 2013;Verma and Chauhan, 2013). A. retroflexus, A. repens C. album and C. arvensis in the present study were similar with the species in the previous studies.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…The results of the present study were also consistent with the results of the studies carried out different region in the world (Dastgheib and Frampton, 2000; Harrington et al, 2002;Hamma and Ibrahim, 2013;Verma and Chauhan, 2013). A. retroflexus, A. repens C. album and C. arvensis in the present study were similar with the species in the previous studies.…”
supporting
confidence: 92%
“…The weeds also harbor insects, diseases and rodents and thus they lower the quality and quantity of apples and may increase the cost of production by causing difficulties during fruit harvest. It is reported that both narrow leaved and broad leaved weeds grow in the apple orchards of Turkey and other apple growing countries of the world and caused problems of orchard management Tepe, l997;Yazlik and Tepe, 2001;Karaca and Guncan, 2003;Akbolat et al,2007;Ustuner and Akyol, 2007;Junk et al1997;Dastgheib and Frampton, 2000;Harington et al 2000).…”
Section: Tamer üStünermentioning
confidence: 99%
“…Other indirect effects are soil compaction incurred during application and decreased soil fertility from loss of soil organic matter (Smith et al 2008, Steenwerth andBelina 2010). Herbicide treatment of the vineyard floor is often restricted to the vine row (10 to 15% of the total vineyard floor), and can involve preemergence and/or postemergence herbicides ("knock-downs") (Lang 1990, Dastgheib andFrampton 2000). Herbicides are mostly used at very low dosage, with sprayers equipped with panels that prevent chemical drift.…”
Section: Herbicidesmentioning
confidence: 99%
“…Facelli and Pickett (1991), as well as Shrestha et al (2002), observed that the type of plant residue cover affected the weed species composition. Consequently, there is a need for future studies to document the response of the weed flora to different cover crops and their mulches (Dastgheib & Frampton, 2000).…”
Section: Introductionmentioning
confidence: 99%